Scholastical Inspirations in Maciej Kazimierz Sarbiewski’s De acuto et arguto - Kwosek, Jacek (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
This article aims at showing scholastical inspirations in Maciej Kazimierz Sarbiewski’s De acuto etarguto. It concerns particularly the view of Sarbiewski at the problem of universals. The author of articleanalyses philosophical contents and scholastical terminology in De acuto et arguto and next he supposes,that Sarbiewski probably could be a moderate realist about universals. Although the text of De acuto etarguto doesn’t settle definitively this question, but Sarbiewski was inspired by Francisco Suarez, who wasa moderate realist about universals to.